1987
DOI: 10.1159/000234432
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Lymph Node Cell Proliferation Induced by Oxazolone

Abstract: The influence of topical exposure to two sensitizing chemicals on draining lymph node cell proliferative responses in BALB/c mice has been examined. Conventional contact sensitization with 4-ethoxymethylene-2-phenyloxazol-5-one (oxazolone) has been shown to induce a rapid and systemic suppression of subsequent proliferative responses to topically applied chemical which can be adoptively transferred to recipient mice with immune lymph node cells. In contrast to some previous reports in which such suppression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Five days later, mice were challenged with oxazolone or vehicle on the dorsum of both ears and proliferative activity measured 3 days later. Stud ies with cultures of draining LNC revealed that, as previously reported [10], exposure to oxazolone at a distant site 5 days prior to challenge with the same chemical, resulted in a marked depression of chal lenge-induced proliferation ( fig. 2A).…”
Section: Induction and Regulation Of Lnc Proliferative Responses To Osupporting
confidence: 67%
See 3 more Smart Citations
“…Five days later, mice were challenged with oxazolone or vehicle on the dorsum of both ears and proliferative activity measured 3 days later. Stud ies with cultures of draining LNC revealed that, as previously reported [10], exposure to oxazolone at a distant site 5 days prior to challenge with the same chemical, resulted in a marked depression of chal lenge-induced proliferation ( fig. 2A).…”
Section: Induction and Regulation Of Lnc Proliferative Responses To Osupporting
confidence: 67%
“…It has been demonstrated previously that, in addi tion to inducing a vigorous primary proliferative re sponse in draining lymph nodes and the development of contact sensitization, topical exposure of mice to oxazolone results in the appearance of immunoregulatory mechanisms which serve to inhibit and con tain proliferative responses [10,11], These homeostatic mechanisms have the ability to influence both primary and secondary responses, and we speculate that their pyhsiological role is in preventing excessive lympho prolifération following the initial and subsequent ex posures to highly immunogenic antigen (such as ox azolone) [11]. The data contained within this report demonstrate that the active regulatory events which result from oxazolone sensitization and which influ ence LNC proliferation are selective for T lympho cytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spontaneous proliferative activity of unfractionated drain ing LNC populations was measured as described previously [20], Briefly, unfractionated suspensions of LNC in RPMI-FCS were seeded into 96-well microtiter plates at a concentration of 2.5 x 106 cells/ml cultured for 24 h at 37°C in a humidified atmosphere of 5% C 0 2 in air with 2 pCi of 5H-methyl thymidine (specific activity 2.5 Ci/mmol; Amersham International, Amersham, UK). Culture was terminated by automatic cell harvesting and 'H-TdR incorpor ation determined by f)-scintillation counting.…”
Section: Measurement O F Lnc Proliferationmentioning
confidence: 99%